Current THD and Output Voltage Ripple Characteristics of Flyback PFC Converters with LED Lamp and Nonlinear RL Loads - Ponniran, Asmarashid; Romai Noor, Mohamad Kamil; Hamdan, Nur Afiqah; Vajravelu, Ashok; Islam, Syed Zahurul; Abd Rahman, Ramhuzaini; Eh Kan, Chessda Uttraphan; Choon, Chew Chang (International Journal of Integrated Engineering, 2023)
This study analysed the characteristics of total harmonic distortion (THD) and output voltage ripple in a flyback PFC converter circuit under two different loads, which are the LED lamp modules and nonlinear RL loads. The converter was designed to step down the AC input voltage (90 V-265 V) to a DC output voltage of 80 V DC for both loads, each with an output power of 16 W. The main objectives were to observe and assess current THD and output voltage ripple for both loads using two different capacitances of the output capacitor, which are 2400 ?F and 6 ?F, respectively. The results demonstrated that using smaller capacitors (6 ?F), it increased output voltage ripple, which it increased for the LED lamp load from 10% to 25% and for the nonlinear RL load it increased from 15% to 70%. However, with the same smaller capacitors (6 ?F), it reduced current THD for both loads, which for the LED lamp load it reduced from 12% to 10.3%, and for the nonlinear RL load it reduced from 13.7% to 8.3%. From these results, with 2400 ?F of the output capacitor, it provided better performance in terms of current THD and output voltage ripple for both load types.